Mesoporous Superconductors: Superconducting Quantum Metamaterials from Convergence of Soft and Hard Condensed Matter Science (Adv. Mater. 26/2021). Issue 26 (1st July 2021) - Beaucage, Peter A.; van Dover, R. Bruce; DiSalvo, Francis J.; Gruner, Sol M.; Wiesner, Ulrich
Abstract : In article number 2006975, mesoporous superconductors are prepared by Ulrich Wiesner and co‐workers via solution‐based block‐copolymer self‐assembly leading to high‐quality quantum metamaterials. The full promise of this soft‐materials approach is realized by producing superconductors with four different mesoscale morphologies. In these materials, the superconducting transition temperatures show variations with mesoscale structure despite nearly identical atomic crystal lattices. The materials exhibit atypical flux avalanches, characteristic of granular materials.